Happier with the Same: Job Satisfaction of Disadvantaged Workers. (29th September 2015) - Perales, Francisco; Tomaszewski, Wojtek
Abstract: Job satisfaction evaluations depend not only on the objective circumstances that workers experience in their jobs, but also on their subjective dispositions, such as their aspirations, expectations, feelings of entitlement or personal evaluation criteria. We use matched employer–employee data from the United Kingdom to examine whether and how subjective dispositions influencing job satisfaction vary across workers with different socio‐demographic traits. We approximate jobs using detailed occupations within workplaces and find that most of the variability in job satisfaction is at the worker rather than the proximate‐job level, and that workers with disadvantaged statuses report higher satisfaction with the same jobs than those with advantaged statuses.